Factors affecting murabahah margin income: evidence from Islamic commercial banks in Indonesia / Ananda Puteri Wahyuni, Ratna Mulyany and Zata Hulwani Zuhri - Wahyuni, Ananda Puteri; Mulyany, Ratna; Zuhri, Zata Hulwani (Universiti Teknologi MARA, 2021)
This study aims to examine factors that influence murabahah margin income. Specifically, it investigates the effect of the Central Bank of Indonesia Rate (BI Rate), Operating Expenses to Operating Income (OEOI), Non-Performing Financing (NPF), and wadiah savings on murabahah margin income at the Islamic Commercial Banks in Indonesia. The method used in this study is quantitative by using the multiple linear regression analysis to test the variables. 12 Islamic Commercial Banks were selected as the sample using a purposive sampling method. With 60 data observations for 5 years, the findings indicate that all the independent variables simultaneously affect the dependent variable. Partially, BI Rate does not affect murabahah margin income, while in contrast, Operating Expenses to Operating Income (OEOI), Non-Performing Financing (NPF), and wadiah savings affect the murabahah margin income.